Pemeliharaan Pentanahan Pada Tower Transmisi Milik PT PLN Persero ULTG Cikupa - Rahima Mahabbah; Endi Permata; Legista Romadhoni Mardillah (Pusat Riset dan Inovasi Nasional, 2023)
Transmission lines are a medium used to transmit electrical energy from generators to consumers who use electricity. One of the components for delivering electric power is the SUTT and SUTET towers. This air duct tower uses a grounding system to protect the tower from external and internal disturbances. One of the disturbances is lightning strikes whose resistance is very large, if a grounding system is not installed it will damage tower components or equipment. The grounding system works to channel the voltage from lightning directly to the earth. The grounding system needs regular maintenance because it is very important to protect the components on the tower in the event of a lightning strike. The maintenance carried out is by measuring the grounding resistance value according to PT PLN standard rules, namely 70 kV transmission network towers are less than or equal to 5 ohms, for 150 kV it is less than or equal to 10 ohms and for 500 kV it is less than or equal to 15 ohm. And maintenance uses drones to see the condition of the GSW (Ground Steel Wire) cable from a height.